Hubungan Antara Dukungan Suami Dengan Pengetahuan Penggunaan Metode Operasi Wanita (Mow) Di Desa Pentur Kecamatan Simo Kabupaten Boyolali - Astuti, Kus Tri, Sulastri, S.Kp., M.Kes (2016)
ABSTRACT The method of operation of women (MOW) or sterilization in women is modern contraception methods previously done by cutting the fallopian tubes (tubes tied) with the development of technological advances MOW can now be done in a way binding on the channel fallopian tubes (tubes tied), so the egg can not move towards ampulla tubes where fertilization can occur low in number of researchers interested in conducting research MOW relationship between husband Support with Knowledge Use of the method of operation in the village woman Pentur District of Simo Boyolali. This study aims to determine the relationship between husband Support with Knowledge Use of the method of operation in the village woman Pentur District of Simo Boyolali. This type of research is quantitative research with Correlasional methods and approach used is cross sectional. This research was conducted in Pukesmas Simo in the village Pentur in April 2016. Population dimaksut and will be used in this research is the EFA yet using the method of operation of women in Puskesmas Simo Boyolali Regency Village EFA Pentur with the number 287. The sample used in this study were 72 respondents. Data analysis techniques using univariate and bivariate. The results showed the husband support the use of the method of operation in the village Pentur women in both categories. Use of the method of operation in the village Pentur women in both categories and are relationship between husband support the use of the method of operation of women in the village of Simo Boyolali District of Pentur indicated by p = (0.000) <0.05. Keywords: Support husband, Operation Methods Women